Quantitative Analysis of Critical Success Factors in the Development of Public-Private Partnership (PPP) Project Briefs in the United Arab Emirates - Rauda Al Saadi; Alaa Abdou; Sabah Alkass (Buildings)
This paper presents the research findings on Public-Private Partnerships (PPP) brief development in the United Arab Emirates. A questionnaire survey was conducted to assess and rank the relative importance of the Critical Success Factors (CSFs) identified in PPP brief development in the UAE. A quantitative analysis was then conducted on the data gathered from the survey, and the results of the analysis are described. The processes of purifying and computing the measurement instruments are also explored using Cronbach’s alpha to assess the reliability of scale measurements. The statistical analysis focuses on the importance and ranking of the identified thirty-eight (38) CSFs and their Sub-Success Factors (SSFs). The overall assessment of these factors highlights their importance in a brief development process. Accordingly, these factors are grouped into seven categories, and the developed CSF framework is presented. The categories, listed in descending order, are Regulatory and Legal Factors; Finance and Economic Factors; Risk-Related Factors; Public Sector Capacity-Related Factors; Procurement-Related Factors; Stakeholder-Related Factors; and Social, Cultural, and Ethical Factors. The research findings offer a comprehensive framework of CSFs for brief development tailored to the unique PPP environment of the UAE to ensure project success.